Telecinematic discourse : approaches to the language of films and television series - Piazza, Roberta; Bednarek, Monika, 1977-; Rossi, Fabio, 1967- (Pragmatics & beyond ;, 2011)
This cutting-edge collection of articles provides the first organised reflection on the language of films and television series across British, American and Italian cultures. The volume suggests new directions for research and applications, and offers a variety of methodologies and perspectives on the complexities of "telecinematic" discourse - a hitherto virtually unexplored area of investigation in linguistics. The papers share a common vision of the big and small screen: the belief that the discourses of film and television offer a re-presentation of our world. As such, telecinematic texts.